2009
DOI: 10.1371/journal.pone.0007926
|View full text |Cite
|
Sign up to set email alerts
|

A Spectrum of Severe Familial Liver Disorders Associate with Telomerase Mutations

Abstract: BackgroundTelomerase is an enzyme specialized in maintaining telomere lengths in highly proliferative cells. Loss-of-function mutations cause critical telomere shortening and are associated with the bone marrow failure syndromes dyskeratosis congenita and aplastic anemia and with idiopathic pulmonary fibrosis. Here, we sought to determine the spectrum of clinical manifestations associated with telomerase loss-of-function mutations.Methodology/Principal FindingsSixty-nine individuals from five unrelated familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
212
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(231 citation statements)
references
References 35 publications
9
212
4
6
Order By: Relevance
“…Interestingly, hepatic syndromes have been associated with hTERT mutations in patients with dyskeratosis congenita. 38 Moreover, two independent studies have revealed experimental evidence that hTERT mutations occur in 3-6% of cirrhosis patients with chronic liver disease (Hartmann et al and Callado et al, Hepatology in press).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hepatic syndromes have been associated with hTERT mutations in patients with dyskeratosis congenita. 38 Moreover, two independent studies have revealed experimental evidence that hTERT mutations occur in 3-6% of cirrhosis patients with chronic liver disease (Hartmann et al and Callado et al, Hepatology in press).…”
Section: Discussionmentioning
confidence: 99%
“…3,10,11 However, the extent of subclinical bone marrow and/or liver disease in patients with ILD and short telomeres has not been previously investigated.…”
Section: For Editorial Comment See Page 1450mentioning
confidence: 99%
“…10 To investigate the degree of associated marrow dysfunction, patients with short telomeres underwent a bone marrow biopsy. Among the 15 patients with short telomeres, 13 (87%) underwent a bone marrow biopsy, and two patients were still completing their lung transplant evaluations at the time of manuscript preparation.…”
Section: Subclinical Bone Marrow Abnormalities In Patients With Ild Amentioning
confidence: 99%
“…(195) Around 8-20% of familial cases of IPF were in responsible of TERC and TERT inherited mutation (196), while 37% of familial cases and 25% of sporadic cases were correlated with shorter telomeres compared to the 10th percentile of the general population, besides as-yet undiscovered genetic or environmental causes (197). Other adult-onset manifestations of impaired telomere maintenance include familial liver cirrhosis (198), aplastic anemia in adulthood (199), and sporadic acute myelogenous leukemia (AML), in which both somatic and germline mutations have been found (200).…”
Section: Telomeres and Diseasesmentioning
confidence: 99%